Selecting Model Parameter to Predict Yield Function in Two Year Old Acacia Bivenosa - Burman, U; Tiwari, J C; Mathur, B K; Harsh, L N; Sharma, S K (Annals of Arid Zone, 2016)
Estimation of yield functions (fuel, fodder and biomass) in 2 year old Acacia bivenosa DC stand under different set of conditions has been reported in this papers. The precise estimate of stem diameter just above ground (immediately prior to branching point) appeared to be reasonable predictor of yield. It has also been observed that planting seedlings of the species in wider spacing, only benefits the height increment.